2007
DOI: 10.1243/09576509jpe468
|View full text |Cite
|
Sign up to set email alerts
|

Tip clearance effect on high-pressure compressor stage matching

Abstract: Tip clearance flows have a major impact on both performance and stability of high-pressure compressors (HPC). The purpose of this paper is to underline how tip clearance variations affect the matching of compressor stages, hence modifying the efficiency and stall margin of the compressor. The practical application covered by the scope of this article is a modern highly loaded HPC dedicated to civil aircraft propulsion.The first part of the paper gives a very simple overview of stagewise matching in multistage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Results showed that the increment in tip gap gradually affected the performance of the unswept blade while the effect was very high for the swept rotors. While carrying out study on high pressure compressor stage matching, Domercq and Escuret [8] and ZhengXian et al [9] deduced that the tip clearance flows and its gap variation have a major impact on performance and stability of high pressure compressors. Tang et al [10] predicted similar behaviour of loss in performance with an increase in tip clearance and they reported an optimum clearance of 6 μm for their specific design.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the increment in tip gap gradually affected the performance of the unswept blade while the effect was very high for the swept rotors. While carrying out study on high pressure compressor stage matching, Domercq and Escuret [8] and ZhengXian et al [9] deduced that the tip clearance flows and its gap variation have a major impact on performance and stability of high pressure compressors. Tang et al [10] predicted similar behaviour of loss in performance with an increase in tip clearance and they reported an optimum clearance of 6 μm for their specific design.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the behaviors of the endwall 3D separation flow could vary significantly as the operating conditions change, including mass-flow rate and rotating speed [1,[13][14][15]. Among the varied influencing factors in multistage environments, the rotor tip clearance flow always plays the most important role in compressor blade row matching [16]. In the experimental work of Ivey et al [17,18], they found that increased rotor tip clearance resulted in significant changes in the performance of the downstream stator.…”
Section: Introductionmentioning
confidence: 99%
“…First, overall performance is largely impacted by the matching conditions between the successive rotor and stator rows (''time-averaged'' flow effects). For instance, rotor tip clearance variations and end-wall flows affect both efficiency [12] and aerodynamic stability [9,26]. Then, relative motions between fixed and rotating parts induce periodic unsteady flows that also modify overall performance, aerodynamic stability and the development of secondary flows [2,3].…”
Section: Introductionmentioning
confidence: 99%